European energy policy: an environmental approach - Morata, Francesc (Elgar, 2012)
"This path-breaking book explores the new European energy policy, highlighting the significance of environmental policy concerns, instruments, and objectives vis-à-vis competing security and market dimensions in order to achieve an all-embracing EU energy policy perspective for the future. While the past years have witnessed unprecedented development of EU energy policy, the understanding of this process has lagged behind. Alongside the scarce literature on this emergent policy, there is also a gap regarding the attention paid to its different components. The study stems from the perception of a mismatch between the valuable debate that certain dimensions of energy policy - namely, energy security and the market and competition framework - have triggered and the neglect of its environmental and climate change dimensions."--Back cover
Enth. 12 Beitr
Literaturangaben
Keywords: Europäische Union; Aufsatzsammlung; Erneuerbare Energien; Energiepolitik; Energiewirtschaft; Europa